Observations of large-amplitude electromagnetic waves and associated wave–particle interactions at the dipolarization front in the Earth's magnetotail: A case study. (July 2015) - Huang, S.Y.; Yuan, Z.G.; Ni, B.; Zhou, M.; Fu, H.S.; Fu, S.; Deng, X.H.; Pang, Y.; Li, H.M.; Wang, D.D.; Li, H.M.; Yu, X.D.
Abstract: Broadband frequency waves around the dipolarization front (DF) are believed to play a crucial role in the particle dynamics. Using the Cluster observations, we report in this study large-amplitude electromagnetic waves with frequencies just above the ion cyclotron frequency at the DF in the near-Earth magnetotail region. The waves have very large amplitudes of magnetic and electric field fluctuations, up to ~2 nT and ~10 mV/m, respectively. The magnetic fluctuations are predominately along the ambient magnetic field (B 0 ), while the electric fluctuations are primarily perpendicular toB 0 . The observed waves are highly oblique with a propagation angle of ~100° with respect to the ambient magnetic field, and are also linearly polarized. These features are consistent with the properties of the ion Bernstein wave mode in the high plasma β region, and also with the properties of current-driven ion cyclotron waves driven by the electromagnetic current-driven Alfven instability. We also discuss the possibility of wave–particle interactions at the DF. Highlights: Larger-amplitude electromagnetic waves were observed at DF. Electromagnetic waves belong to Ion Bernstein mode or current-driven ion cyclotron mode. The observed electromagnetic waves cannot accelerate the protons at the survival timescale of the DFs and the waves.